Phenomenological Analysis of PSAK 101 on the Financial Statements of BMTs in Medan - Nadia, Nadia; Susanti, Widya; Samri Juliati Nasution, Yenni; Marliyah, Marliyah (STAIN MAJENE, 2025)
This study aims to analyze the implementation of the Statement of Financial Accounting Standards (PSAK) 101 concerning the Presentation of Islamic Financial Statements in Islamic cooperatives in Medan City. The research focuses on four main aspects recognition, measurement, presentation, and disclosure of financial statements. A qualitative approach with a phenomenological method was employed to explore in depth the experiences, understanding, and perceptions of Islamic cooperative managers in applying PSAK 101. The research subjects consist of three Islamic microfinance institutions: BMT Masyarakat Madani Sumatera Utara, BMT Al-Musabbihin, and BMT Mandiri Abadi Syariah. Data were collected through interviews, observations, and documentation. The findings reveal that the implementation of PSAK 101 in the three Islamic cooperatives remains suboptimal. In terms of recognition, the temporary syirkah funds have not been properly segregated. Regarding measurement, all cooperatives still use the historical cost basis without asset revaluation as required by PSAK 16. In presentation, financial statements only include the balance sheet, income statement, and changes in equity, while the other seven components required by PSAK 101 are not presented. The disclosure aspect is also weak, as there are no notes to the financial statements and several account classifications are incorrect. The limited implementation of PSAK 101 is influenced by a lack of understanding among management regarding Islamic accounting standards, insufficient technical training, and limited human resources with expertise in Islamic accounting. This study recommends strengthening Islamic accounting training, developing PSAK 101-based accounting software, and enhancing the role of the Sharia Supervisory Board in ensuring compliance with Sharia principles.